Consistent Symbiodiniaceae community assemblage in a mesophotic-specialist coral along the Saudi Arabian Red Sea - Vimercati, Silvia; Terraneo, Tullia I.; Castano, Carolina Bocanegra; Barreca, Federica; Hume, Benjamin C. C.; Marchese, Fabio; Ouhssain, Mustapha; Steckbauer, Alexandra; Chimienti, Giovanni; Eweida, Ameer A.; Voolstra, Christian R.; Rodrigue, Mattie; et al. (Frontiers in Marine Science, 2024)
The Red Sea is a narrow rift basin characterized by latitudinal environmental gradients which shape the diversity and distribution of reef-dwelling organisms. Studies on Symbiodiniaceae associated with select hard coral taxa present species-specific assemblages and concordant variation patterns from the North to southeast Red Sea coast at depths shallower than 30 m. At mesophotic depths, however, algal diversity studies are rare. Here, we characterize for the first time host-associated algal communities of a mesophotic specialist coral species, Leptoseris cf. striatus, along the Saudi Arabian Red Sea coast, spanning the eastern Red Sea coastline from the Northern Red Sea to the Farasan Banks in the South, and across two sampling periods, Fall 2020 and Spring 2022. We used Next Generation Sequencing of the ITS2 marker region in conjunction with SymPortal to denote algal assemblages. Our results show a relatively stable coral species-specific interaction with algae from the genus Cladocopium along the examined latitudinal gradient, with the appearance, in a smaller proportion, of presumed thermally tolerant algal taxa in the genera Symbiodinium and Durusdinium during the warmer season (Fall 2020). Contrary to shallow water corals, our results do not show a change in Symbiodiniaceae community composition from North to South in this mesophotic specialist species. However, our study highlights for the first time that symbiont communities are subject to change over time at mesophotic depth, which could represent an important phenomenon to address in future studies.